Correction: Intrinsically ferromagnetic Fe-doped TiO2 coatings on titanium for accelerating osteoblast response in vitro. Issue 39 (3rd October 2018) - Li, Kai; Yan, Ting; Xue, Yang; Guo, Lijun; Zhang, Lan; Han, Yong
Abstract : Correction for 'Intrinsically ferromagnetic Fe-doped TiO2 coatings on titanium for accelerating osteoblast response in vitro ' by Kai Li et al., J. Mater. Chem. B, 2018, DOI: ;10.1039/c8tb01414k .